The Legal Maxim al-Darurat Tubih al-Mahzurat in Innovative Zakat Utilization for the Economic Empowerment of the Ummah - TB Rifat; Ahmad Hasan Ridwan; Dede Rohayati; Eid Abdul Aziz (UIN Siber Syekh Nurjati Cirebon, 2026)
Structural poverty requires zakat institutions to move beyond short-term relief while continuing to protect the legal entitlements of mustahik. This study examines the legal boundaries for applying the maxim al-Ḍarurat Tubiḥ al-Maḥẓurat to innovative forms of productive zakat and formulates a Sharia-compliant implementation framework. It employs normative Islamic legal research using conceptual, comparative, statutory, fatwa, and maqāṣid al-Sharia approaches. Primary and secondary legal materials were collected through documentary analysis and examined through data condensation, data display, and conclusion drawing and verification. The findings demonstrate that the maxim does not provide a general justification for all productive zakat programs because productive zakat is not inherently prohibited. Nonrepayable business capital grants and capacity-building programs may be justified by tamlīk, maṣlaḥah, and maqāṣid al-Sharia. By contrast, delayed distribution, institutional investment, and collectively managed productive assets require stricter tests of necessity, proportionality, governance, and beneficiary protection. Repayable revolving schemes should primarily use infaq, sadaqah, waqf, or other non-zakat funds because zakat transferred through valid tamlīk becomes the property of the mustahik. The study proposes a Sharia legal test based on mustahik eligibility, fulfillment of basic needs, the form of tamlīk, degree of necessity, availability of lawful alternatives, proportionality, Sharia governance, and program evaluation. This framework enables zakat institutions to promote sustainable economic empowerment without diminishing the rights and dignity of mustahik.